2018
DOI: 10.1103/physreva.97.043621
|View full text |Cite
|
Sign up to set email alerts
|

Dark-dark-soliton dynamics in two density-coupled Bose-Einstein condensates

Abstract: We study the 1D dynamics of dark-dark solitons in the miscible regime of two density-coupled Bose-Einstein condensates having repulsive interparticle interactions within each condensate (g > 0). By using an adiabatic perturbation theory in the parameter g12/g, we show that, contrary to the case of two solitons in scalar condensates, the interactions between solitons are attractive when the interparticle interactions between condensates are repulsive g12 > 0. As a result, the relative motion of dark solitons wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The dark soliton state is a free state, and it admits a wide non-zero density background. This character is admitted by most of previous vector solitons in BECs systems [4][5][6][7][8][9]. We would like to look for nondegenerate bound state solitons (NDBSSs), for which all eigen-states are bound states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark soliton state is a free state, and it admits a wide non-zero density background. This character is admitted by most of previous vector solitons in BECs systems [4][5][6][7][8][9]. We would like to look for nondegenerate bound state solitons (NDBSSs), for which all eigen-states are bound states.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-component coupled Bose-Einstein condensates (BECs) provide a good platform to study the dynamics of vector solitons [1]. Many different vector solitons have been obtained in the two-component coupled BEC systems, such as the bright-bright soliton [2,3], the bright-dark soliton [4], the dark-antidark soliton [5], the dark-dark soliton [6,7], and the dark-bright soliton [8,9]. The soliton states can be related with eigen-states in quantum well [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realization of two-component BECs [7][8][9] has opened a window towards the study of more complex solitonic structures [10][11][12][13][14][15][16][17][18][19]. In repulsive two-component BECs, a fundamental excitation takes the form of a dark-bright (DB) soliton [10].…”
Section: Introductionmentioning
confidence: 99%
“…The first experimental realizations of DB solitons in BECs almost a decade ago [14,[27][28][29][30][31], as well as subsequent experimental realizations of their variants and generalizations [15,19,[32][33][34][35] have motivated a significant amount of interest in studying their dynamics and interactions [18,[36][37][38][39][40][41][42][43][44][45][46][47]. In particular, several methods have been proposed to create DB soliton structures.…”
Section: Introductionmentioning
confidence: 99%
“…confinement) balances the repulsive interaction between them [23]. Interestingly, it has been recently reported that in systems with two overlapped BECs the intersoliton forces can show either repulsive or attractive character depending on the sign of the interatomic interactions between condensates [29].…”
Section: Introductionmentioning
confidence: 99%